(untitled) (Revista Contexto & Saúde, 2022)
Objective: To carry out a nutritional intervention through the construction and implementation of the Technical Preparation Form focusing on the adequacy of the supply of sodium and lipids in food preparations. Step 1. Diagnosis: Analysis of the amount of lipid using the technique of extraction using the Soxhlet and sodium apparatus by weighing the amount of added salt used and calculating the amount of sodium using the Brazilian Table of Food Composition and, application of script to observe the preparation method. Step 2. Intervention: Development and implementation of the Technical Preparation Sheets using the model recommended by the National School Feeding Program. Step 3. Evaluation of acceptability by students according to the Program manual, analysis of the use of Technical Preparation Sheets by the observation script and analysis of the quantity by the method already mentioned above. An adequate lipid and sodium value of 67.5% was observed above that recommended by the program for two meals (up to 600 mg). After the implementation of the technical preparation sheets, the amount of sodium was reduced to 26.4% of the recommendation and that of lipid remained adequate. The intervention was effective in promoting a standardization of rice and bean production through the Technical Preparation Form with an adequate amount of oil and added salt, promoting greater nutritional quality.